TERM OF ADDRESS IN BAJAWA DIALECT OF NGADA LANGUAGE - Loda, Wilhelmina; Bay, Jenny Ronawati; Semiun, Thresia Trivict (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
This study aimed at describing the types of greetings action used by Bajawanesse in their daily conversations. This study applied descriptive qualitative method.The data were collected from two resources, they were the writer herself and the informants. The instrument used to collect the data was structure interview. The result of the study showed that there are four kinds ofthe terms of address used in Bajawa dialect of Ngada Language. First is the form ,there are some aspects in the use of the term off address.The fisrt category refers to the higher status, the second refers to the same status and the third refers to the lower status.Second is, the distribution of the terms of address in Bajawa dialect of Ngada Language there are two posibillities, it can be appears in the initial position as well as in final position depen not only on context but also in the intensity of meaning. The terms of address used in Bajawa dialect of Ngada Language serve a number of functions covering the politeness markers, honorofic and the intimacy depending on the paarameters of social status, age, gender and situation.The meaning of the terms of address used in Bajawadialect of Ngada language are closely related to their forms, distributions and function considering with their context of uses in Ngada culture for the reason that the uses od terms of address are culturally bound.